2022
DOI: 10.7759/cureus.21668
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal Neuralgia As the Principal Manifestation of Anaplasmosis: A Case Report

Abstract: Unlike the tick-borne diseases ehrlichiosis and Lyme disease, human granulocytic anaplasmosis is rarely associated with neurological complications. In this case report, we present a patient who developed a severe, lancinating headache shortly after known tick exposure. A tick-borne PCR panel was positive for Anaplasmosis phagocytophilum and neurology evaluation yielded a concomitant diagnosis of new-onset trigeminal neuralgia. Our case explores the relationship between anaplasmosis infection and trigeminal neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Many of these overlapping factors on the MSIDS map were increasing underlying symptomatology, apart from her tick-borne infections since hypoglycemia, Candida, POTS, low adrenal function, chronic insomnia, depression, low glutathione levels, vitamin and mineral deficiencies, heavy metal toxicity, and possible mitochondrial dysfunction can all increase underlying fatigue and affect mood [170][171][172][173][174][175][176][177][178][179]. Similarly, infections with Borrelia, Bartonella, and Anaplasma, heavy metal toxicity, i.e., mercury (Hg), lead (Pb), and arsenic (As), mold toxicity, vitamin B deficiency, and mitochondrial dysfunction can all cause neurological symptoms and increase neuropathy [180][181][182][183][184][185][186], which is why a full MSIDS evaluation in CLD/PTLDS is highly important for diagnosing and treating all potential overlapping etiologies. A laboratory clue that Bartonella was also playing a significant role in her chronic illness was that she had an indeterminate Bartonella Western blot and evidence of prior exposure to Bartonella vinsonii sub spp.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these overlapping factors on the MSIDS map were increasing underlying symptomatology, apart from her tick-borne infections since hypoglycemia, Candida, POTS, low adrenal function, chronic insomnia, depression, low glutathione levels, vitamin and mineral deficiencies, heavy metal toxicity, and possible mitochondrial dysfunction can all increase underlying fatigue and affect mood [170][171][172][173][174][175][176][177][178][179]. Similarly, infections with Borrelia, Bartonella, and Anaplasma, heavy metal toxicity, i.e., mercury (Hg), lead (Pb), and arsenic (As), mold toxicity, vitamin B deficiency, and mitochondrial dysfunction can all cause neurological symptoms and increase neuropathy [180][181][182][183][184][185][186], which is why a full MSIDS evaluation in CLD/PTLDS is highly important for diagnosing and treating all potential overlapping etiologies. A laboratory clue that Bartonella was also playing a significant role in her chronic illness was that she had an indeterminate Bartonella Western blot and evidence of prior exposure to Bartonella vinsonii sub spp.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to CNS, the peripheral nerves can be damaged in patients with anaplasmosis. Cases of trigeminal neuralgia [ 14 ], brachial plexopathy [ 15 ], transient hearing loss [ 16 ], and bilateral facial nerve paralysis [ 17 ] have been reported. A recent systematic review of published cases on anaplasmosis also reported cases of peripheral neuropathy at the site of the tick bite [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…While meningitis and neurological symptoms have been reported with human monocytic ehrlichiosis (HME), this is a rarer occurrence in HGA 13–16. The presence of inclusion bodies in the monocytes of CSF has been documented in several patients with HME 17.…”
Section: Discussionmentioning
confidence: 99%